2011
DOI: 10.1038/npp.2011.249
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Reverses Phencyclidine-Induced Desynchronization of Prefrontal Cortex through a 5-HT1A Receptor-Dependent Mechanism

Abstract: The non-competitive NMDA receptor (NMDA-R) antagonist phencyclidine (PCP)Fused as a pharmacological model of schizophreniaFdisrupts prefrontal cortex (PFC) activity. PCP markedly increased the discharge rate of pyramidal neurons and reduced slow cortical oscillations (SCO; 0.15-4 Hz) in rat PFC. Both effects were reversed by classical (haloperidol) and atypical (clozapine) antipsychotic drugs. Here we extended these observations to mice brain and examined the potential involvement of 5-HT 2A and 5-HT 1A recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 94 publications
4
30
0
Order By: Relevance
“…Likewise, the reversal of this effect by two antipsychotic drugs with different primary targets strongly suggests a relationship with their therapeutic action. Despite its low in vitro affinity for 5-HT 1A receptors, the reversal by clozapine of PCP effects depends on the in vivo stimulation of such receptors (Kargieman et al, 2012), as previously observed for the antipsychotic-evoked release of dopamine in mPFC (Diaz-Mataix et al, 2005). …”
Section: Serotonin Modulates Cortical Network Activitymentioning
confidence: 73%
“…Likewise, the reversal of this effect by two antipsychotic drugs with different primary targets strongly suggests a relationship with their therapeutic action. Despite its low in vitro affinity for 5-HT 1A receptors, the reversal by clozapine of PCP effects depends on the in vivo stimulation of such receptors (Kargieman et al, 2012), as previously observed for the antipsychotic-evoked release of dopamine in mPFC (Diaz-Mataix et al, 2005). …”
Section: Serotonin Modulates Cortical Network Activitymentioning
confidence: 73%
“…The 5-HT 1A effect, which parallels the post-mortem data cited in the "Introduction", suggest the possibility that subchronic PCP treatment impairs cortical 5-HT release, leading to an upregulation of post-synaptic 5-HT 1A receptors, which may contribute to the efficacy of 5-HT 1A agonists in this model. It is noteworthy that the efficacy of clozapine to prevent PCPinduced desynchronization of PFC is dependent upon 5-HT 1A activation, but not 5-HT 2A blockade (Kargieman et al 2011), a further evidence for the important role of 5-HT 1A agonism to ameliorate hypoglutamatergic deficits. The results reported here also indicate that the combination of 5-HT 1A partial agonism and 5-HT 2A antagonism is insufficient to reverse the PCP-induced NOR deficit.…”
Section: Discussionmentioning
confidence: 93%
“…124125 More recently, it was shown that the ability of clozapine to reverse phencyclidine-elicited cortical desynchronization—a model of neural activity underlying negative symptoms— requires activation of 5-HT 1A receptors. 126 …”
Section: Pharmacology and Adverse Eventsmentioning
confidence: 99%